A technique for total skin electron therapy (TSET) of an anesthetized pediatric patient. (29th September 2018) - Kron, Tomas; Donahoo, Grace; Lonski, Peta; Wheeler, Greg
Abstract: Purpose: Total skin electron therapy (TSET) is a technique to treat cutaneous lymphomas. While TSET is rarely required in pediatric patients, it poses particular problems for the delivery. It was the aim of the present work to develop a method to deliver TSET to young children requiring anesthetics during treatment. Methods: A customized cradle with a thin window base and Poly(methyl‐methacrylate) (PMMA) frame was built and the patient was treated in supine position. Two times six fields of 6 MeV electrons spaced by 60° gantry angles were used without electron applicator and a field size of 36 × 36 cm 2 . The two sets of six fields were matched at approximately 65% surface dose by rotating the patient around an axis 30 cm distance from beam central axis, effectively displacing the two sets of fields in sup/inf direction by 60 cm. Electron energy was degraded using a 12 mm PMMA block on the gantry. Focus to skin distance was maximized by displacing the patient in opposite direction of the beam resulting in a different couch position for each field. Results: A 2‐yr‐old patient was treated in 12 fractions of 1.5 Gy over 2.4 weeks. Dose to skin was verified daily using thermoluminescence dosimetry and/or radiochromic film. The treatment parameters were adjusted slightly based on in vivo dosimetry resulting in a dose distribution for most of the treatment volume within ±20% of the prescribed dose. Six areas were boosted using conventional electron therapy. Conclusion: TSET can be delivered to pediatric patients using a customized couch top on a conventional linear accelerator.